ON THE PRECIPICE OF NAIROBI PROCESS FAILURE: EAST AFRICAN COMMUNITY’S CHALLENGES TO REALIZE PEACE IN DEMOCRATIC REPUBLIC OF CONGO - Nur Azizah; Muhammad Rey Dafa Ahmadi (Faculty of Social and Political Sciences, Universitas Diponegoro, 2024)
Since 1997 the Democratic Republic of Congo (DRC) has been facing armed conflicts between ethnic groups which was triggered by land conflicts and gold and cobalt mine posession control on East Congo. Interventions done by other countries to support rebellions expanded the scale of coflict and got labeled as The African World War. The conflict, which entangled African countries around Great Lakes forced East African Community (EAC) to intervene with the peace treaty known as the Nairobi Process in 2021. This article aims to convey the EAC's initiative to bring about peace in the DRC, and the challenges it faces. This study employs a literature study method, drawing on secondary data released in the form of press conferences, reports from international organizations, journals, newspapers, and books. The outcomes of this study reveal that the EAC was successful in asking the parties of the dispute to engage in negotiations known as the Nairobi Process, which allows the EAC the ability to put together and deploy a peacekeeping force by 2021. But stability did not last long as DRC government only used EAC peacekeeping force as additional force to drive away the M23 rebels. When the objective wasn’t met and EAC peacekeeping force was unable to carry out supervision and disarmament mission, DRC government expelled EAC peacekeeping force from DRC. M23 rebels still control cobalt and gold mines in the east of DRC.